Carbonic anhydrase inhibition by acetazolamide reduces in vitro epileptiform synchronization. (August 2015) - Hamidi, Shabnam; Avoli, Massimo
Abstract: Depolarizing GABAA receptor-mediated currents are contributed by HCO3 − efflux, and play a role in initiating ictal-like epileptiform events in several cortical structures supporting the view that GABAA receptor signaling actively participates to epileptiform synchronization. We employed here field potential recordings to analyze the effects of the carbonic anhydrase inhibitor acetazolamide (10 μM) on the epileptiform activity generated in vitro by piriform and entorhinal cortices (PC and EC, respectively) during application of the K + channel blocker 4-aminopyridine (4AP, 50 μM). Under these experimental conditions ictal- and interictal-like discharges along with high-frequency oscillations (ripples: 80–200 Hz, fast ripples: 250–500 Hz) occurred in these two regions. In both PC and EC, acetazolamide: (i) reduced the duration and the interval of occurrence of ictal discharges along with the associated ripples and fast ripples; (ii) decreased the interval of occurrence of interictal discharges and the rates of associated fast ripples; and (iii) diminished the duration and amplitude of pharmacologically isolated GABAergic events while increasing their interval of occurrence. Our results indicate that acetazolamide effectively controls 4AP-induced epileptiform synchronization in PC and EC. We propose that this action may rest on decreased GABAA receptor-mediated HCO3 − efflux leading to diminished depolarization of principal cells and, perhaps, of interneurons. Highlights: Acetazolamide reduced the duration and the interval of ictal events. Acetazolamide decreased the interval of occurrence of interictal events. Rate of ripples and fast ripples were reduced after acetazolamide application. Acetazolamide decreased the duration of isolated GABAergic events.